Preventing Stunting Through Effective Supplementary Feeding - Anjelina, Poppy; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Stunting is a significant public health issue that adversely affects child growth and development, particularly in developing countries like Indonesia, leading to increased morbidity and mortality rates. Specific Background: In Kedung Peluk Village, Sidoarjo Regency, the Supplementary Feeding Program (PMT) was implemented to combat stunting, but its effectiveness remains uncertain. Knowledge Gap: There is limited research evaluating the specific effectiveness of PMT in this context, necessitating a thorough examination. Aims: This study analyzes the effectiveness of PMT in preventing stunting in Kedung Peluk Village, focusing on indicators such as target accuracy and program understanding. Results: While PMT is well-targeted and timely, many community members lack understanding of stunting prevention. Although the number of stunted children decreased from 15 to 9, awareness of nutritional needs remains low. Novelty: This research offers new insights into PMT's effectiveness in a rural setting, highlighting community perceptions. Implications: The findings emphasize the need for improved educational initiatives to enhance community understanding and engagement, ultimately aiming to reduce stunting rates. Highlights: Effectiveness Evaluation: The study assesses PMT's impact on reducing stunting rates among children in Kedung Peluk Village. Community Awareness: Significant gaps exist in community understanding of nutritional needs and stunting prevention. Educational Initiatives: Enhanced educational strategies are crucial for improving engagement and knowledge about stunting in the local population. Keywords: Stunting, Child Nutrition, Public Health, Providing Supplementary Food (PMT)